Sistem Pendukung Keputusan Untuk Penentuan Calon Pelamar Kerja Dan Perusahaan Dengan Menggunakan Metode Simple Additive Weighting (Studi Kasus : STIKOM CAREER CENTER (SCC) Surabaya) - Hosama, Novita; Widodo, Arifin Puji; Sutanto, Teguh (Jurnal JSIKA, 2012)
The problems currently faced by STIKOM Career Center (SCC) is not having a record of their competence by alumni and corporate data, the absence of a means for performing filtering based on competency of graduates to find appropriate jobs that SCC does not have information about the competencies alumni and the number of competencies required by the company. Based on these problems it is necessary an information system web based job which has a function as a means to accommodate the data of alumni and their competencies and corporate data and their jobs will be offered, as well as the competence graduates can do the filtering based on the calculation method Simple Additive weighting (SAW) where each competency will have weight and can generate reports on the number of competencies required by the company. Web-based information systems can be used to manage corporate data and competencies alumni, capable of displaying a list of alumni in accordance with its competence and result in a report on the number of competencies required by the company. With the web-based information system, the flow of information regarding the competence graduates can be channeled in the search for a suitable job. Keywords: Alumni Competence, Jobs, Simple Additive Weighting (SAW)